Mampukah kepuasan konsumen memediasi pengaruh personal selling, direct selling dan nilai-nilai Islam terhadap loyalitas nasabah? - Warindrasti, Ragina; Pratama, Abdul Aziz Nugraha (Journal of Management and Digital Business, 2021)
This study aims to examine the effect of personal selling, direct selling, and Islamic values on customer loyalty at BPRS Sukowati Sragen with customer satisfaction as an Intervening Variable. The number of samples taken in this study was 100 respondents as a sample using the random sampling technique. The tool used in this research is Path Analysis. The results showed personal selling did not affect loyalty. Direct selling had a positive effect on customer loyalty, while Islamic values had no effect on customer loyalty and satisfaction had a positive effect on customer loyalty at BPRS Sukowati Sragen. Satisfaction does not mediate the influence of Islamic values on loyalty, but it is able to mediate personal selling and direct selling on loyalty.